Earth Collective. Natural Conditions for a Transindividual Politics (Itinera, 2023)
The concept of a transindividual relation has been articulated in order to resolve the problem of the unity of individuals in association with others. More particularly, it has been offered as a route for overcoming a disjunctive tendency whereby either individuality is lost to an encompassing collective, or the substance of the individual renders the collective accidental, optional, or a mere semblance. Transindividuality thus offers a way to think individuals and collectives thereof as relative, mutually dependent and constitutive, whilst maintaining a separation between the two. Equally, it affords a conception of a collective which is more than the sum of its parts, or an arbitrary aggregate of beings.Whilst this abstract description of transindividuality might appear apt for ecological or earth systems analysis, to date this has not been attempted. Neither of the two most significant thinkers of transindividuality, Gilbert Simondon and Étienne Balibar, broach the question of a natural transindividual at any length, nor do the various monographs and special editions of journals which have been dedicated to extending and criticising the former authors’ analysis of transindividuality. As such, this article addresses this lacuna through discussion of the problem of natural transindividuality, claiming that mutual dependency and constitution between individuals and collectives pertains to geophysical and vital relations as much as it does to human social relations.
Keywords: Simondon, Balibar, Transindividual, Gaia, Ecology.